2011
DOI: 10.1080/17429145.2010.545147
|View full text |Cite
|
Sign up to set email alerts
|

Effect of inoculation with a thermotolerant plant growth promotingPseudomonas putidastrain AKMP7 on growth of wheat (Triticumspp.) under heat stress

Abstract: The present study was carried out to investigate the effect of plant growth promoting thermotolerant Pseudomonas putida strain AKMP7 on the growth of wheat plants to heat stress. The results indicated the superior performance by P. putida strain AKMP7 in improving survival and growth of wheat plants under heat stress. The bacterium significantly increased the root and shoot length, dry biomass, tiller, spike let and grain formation of wheat over uninoculated plants. Inoculation reduced membrane injury and the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

7
75
0
1

Year Published

2014
2014
2020
2020

Publication Types

Select...
4
3
2

Relationship

0
9

Authors

Journals

citations
Cited by 194 publications
(91 citation statements)
references
References 40 publications
7
75
0
1
Order By: Relevance
“…Inoculated plants had increased biomass, shoot and root length, and seed size. ROS generation under stress treatment was also lessened, with lower levels of expression observed for ROS response genes such as superoxide dismutase, ascorbate peroxidase, and catalase [45]. Similar results have been found with sorghum and other Pseudomonas putida AKMP strains [46].…”
Section: Key Mechanisms Targeted By Humic and Fulvic Acid Based Biostsupporting
confidence: 80%
“…Inoculated plants had increased biomass, shoot and root length, and seed size. ROS generation under stress treatment was also lessened, with lower levels of expression observed for ROS response genes such as superoxide dismutase, ascorbate peroxidase, and catalase [45]. Similar results have been found with sorghum and other Pseudomonas putida AKMP strains [46].…”
Section: Key Mechanisms Targeted By Humic and Fulvic Acid Based Biostsupporting
confidence: 80%
“…Comparing the effect of rhizobacterial isolates, the TAN1 showed maximum root length than other isolates and uninoculated control (Figure 1). Ali et al (2011) found that inoculation of PGPR significantly increased the root and shoot length and dry biomass of wheat over uninoculated plants. Significant increases in growth and in yield of agronomically important crops in response to inoculation with PGPR have been found in an experiment at Recife, Brazil (Figueiredo et al 2008).…”
Section: Discussionmentioning
confidence: 93%
“…Wheat (T. aestivum) [202] Heat stress Pseudomonas putida AKMP7 Wheat (Triticum spp) [98] Temperature Pseudomonas fluorescens, Pantoea agglomerans, Mycobacterium sp Wheat (T. aestivum) [203] Salinity Azospirillum Wheat (T. aestivum) [62] Salinity Pseudomonas putida, Pseudomonas extremorientalis, Pseudomonas chlororaphis and Pseudomonas aurantiaca.…”
Section: Bacillus Amyloliquefaciens and Azospirillum Brasilensementioning
confidence: 99%
“…[95][96][97]. Ali et al used P. putida AKMP7 resulting in significant increase in proline levels in heat-stressed wheat plants [98].…”
Section: Accumulation Of Osmolytesmentioning
confidence: 99%